COMPARATIVE ANALYSIS OF FEASIBILITY AND RELIABILITY OF PIM 3 SCORE VS. TRADITIONAL SCORING SYSTEMS: INSIGHTS FROM A SINGLE INSTITUTION - HAREESH; HASEEB, ABDUL; MALASHETTY, SHARANABASAPPA (International Journal of Current Pharmaceutical Research, 2024)
Objective: This comparative analysis explores the feasibility and reliability of the Pediatric Index of Mortality 3 (PIM 3) Score in contrast to traditional scoring systems within the context of a single institution. The study delves into the intricate landscape where the contemporary PIM 3 score converges with the time-honored methodologies of conventional scoring systems, offering valuable insights into prognostic evaluation. Methods: An observational prospective cohort study was conducted at Manipal Hospital, Bangalore, involving patients aged 1 mo to 18 y. The study focused on children admitted to the Pediatric Intensive Care Unit (PICU) for at least 1 hour, studying the feasibility of obtaining PIM 3 scores within the first hour. Exclusion criteria included neonates, infants less than one-month-old, and children requiring elective procedural sedation. Feasibility was assessed, and logistic regression was employed to evaluate PIM 3's ability to discriminate between survivors and non-survivors. Results: The training dataset comprised 2,534 patients with a mean age of 8.2 y. Patient characteristics, including age, gender, race, patient type, and origin, were well-distributed. Trauma and variables like elective admission and mechanical ventilation in the first hour were infrequent. The mortality rate across datasets was 1.0%. The PIM 3 risk of mortality and PICU medical length of stay were calculated, forming a comprehensive overview of patient profiles. Conclusion: The comparative analysis unfolds as a cerebral sojourn, revealing the intricate dance of perplexity and burstiness in the juxtaposition of PIM 3 score against traditional scoring systems. The study contributes nuanced insights, portraying each word and concept as integral notes in the composition of knowledge. This singular institutional perspective offers a profound understanding into the intricacies of prognostic evaluation, creating a narrative that transcends conventional methodologies.